Medial preoptic sexual dimorphisms in the guinea pig. I. An investigation of their hormonal dependence - Byne, W (J Neurosci, 1987)
The guinea pig exhibits sexually dimorphic patterns of cell density and distribution throughout the medial preoptic area, a region that has been shown to be involved in the regulation of sexually differentiated behavioral and endocrinological reproductive functions (Bleier et al., 1982). The most prominent sex differences involve 2 components of the medial preoptic nucleus (MPN), an anteriorly placed compact subnucleus (MPNa) that is twice as large in females as in males, and a centrally placed compact subnucleus that occupies an approximately 10-fold greater volume in males than in females and corresponds to the sexually dimorphic nucleus described in the rat by Gorski et al. (1978). In the present study the sex differences in both of these cell groups were shown to be unaffected by neonatal gonadectomy and postnatal hormonal manipulations. In contrast, MPNa volume was significantly decreased and MPNc volume significantly increased in genotypic females exposed to testosterone propionate (TP) on gestational days 28-37 or 28-65 but not 38-65. All 3 prenatal TP treatments administered to females significantly increased mounting frequencies and suppressed lordosis, ovulation, and the positive-feedback effects of estrogen and progesterone on luteinizing hormone release. Thus, the volumetric sex differences in MPNa and MPNc alone do not seem to be sufficient to account for the sex differences in the functions of the medial preoptic region. It is, therefore, suggested that androgens continue to exert organizational influences upon the developing brain after cytoarchitectonic patterns have been determined.